Design Optimization of Universal Joints for All-Terrain Vehicles. Issue 1 (April 2021) - Yanda, Sagar; Bala Murali, Gunji; Shankar raju, Siva; Jason Duckworth, Bill; Sen, Chandra; Singh Chadha, Sidakdeep
Abstract: Universal joint mechanism widely used in the automobile power transmission systems. This joint mechanism desired to permit some angular deviations along the axis of rotation. The cardan joint comprises of the three main parts including the input drive shaft, the output drive shaft and the cross like piece. Two points of the cross piece connect to the input drive shaft and two other points connect to the output drive shaft. Connections are provided by the needle bearings. It is an important aspect of these bearings that while in action they never go through complete cycles. In other words, each of these bearings revolves only a few degrees around its axis before returning to its original position. The paper aims to develop a UV joint that is suitable for All-Terrain Vehicles (ATVs). These types of vehicles have to traverse rough terrain and hence require taller suspension set up. Conventional universal joints limit this ability as the allowable articulation angle is very less. Due to this, they are prone to wear and malfunction and need to be replaced in comparatively short intervals of time. Naturally, it means that such parts have limited life span. We have hence developed a UV joint design which allows for better articulation angle while maintaining strength and reducing weight at the same time.